INACCURACY OF NONINVASIVE BLOOD PRESSURE MONITOR DEVICES, DO WE HAVE AN ALTERNATIVE? - Aisha Khan Jadoon; Fasiha Sohail; Arzu Jadoon; Sumera Nawaz Qabulio (ziauddin University, 2019)
Background: Blood pressure (BP) is obligatorily measured each time a patient visits Emergency room (ER) or is admitted in ICU/CCU. Accuracy of blood pressure measurement in clinical settings is the key to appropriate diagnosis of hypertension in a patient. It remains elusive, however, whether oscillatory automated BP measurement yields lower values than auscultatory manual methods. It has been witnessed that both the devices give different readings of the same patient at one point in time. This study helped to determine the accurate or more reliable of the two devices. Methods: A double-blind randomized clinical cross over trial was carried out at Ziauddin University Hospital from February 2018 to June 2018. Sample of 100 was taken through random sampling. The device used in this study was the Dinamap Procare 100. SPSS 20 was used for data entry and analysis. Results: The mean of difference in systolic manual Blood Pressure (sMBP) and systolic automated Blood Pressure (sABP) was estimated to be 15.62 with a standard deviation of ± 8.57, while the mean of difference in diastolic MBP and ABP was 12.6 with a standard deviation of ± 24.7. Both systolic and diastolic readings were far low by automated devices in comparison to Manual devices. Conclusion: The results of this study suggested that automated method in measurement of BP frequently shows lower BP. This can influence diagnosis of hypertension and management of certain medical conditions.